2019
DOI: 10.3390/en12203805
|View full text |Cite
|
Sign up to set email alerts
|

Separation Flow Control of a Generic Ground Vehicle Using an SDBD Plasma Actuator

Abstract: Quiescent flow and wind tunnel tests were performed to gain additional physical insights into flow control for automotive aerodynamics using surface dielectric barrier discharge plasma actuators. First, the aerodynamic characteristics of ionic wind were studied, and a maximum induced velocity of 3.3 m/s was achieved at an excitation voltage of 17 kV. Then, the optimal installation position of the actuator and the influence of the excitation voltage on flow control at different wind speeds were studied. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…From the 6 SJA method, neither DR nor Count values had connection with the St values. From St 0.1 [47] 12.1 [10], it had low and high reductions, which made it difficult to establish general connection to the actuation frequency, though it supports Kourta et al [14]'s findings.…”
Section: Quantitative Analysismentioning
confidence: 70%
See 2 more Smart Citations
“…From the 6 SJA method, neither DR nor Count values had connection with the St values. From St 0.1 [47] 12.1 [10], it had low and high reductions, which made it difficult to establish general connection to the actuation frequency, though it supports Kourta et al [14]'s findings.…”
Section: Quantitative Analysismentioning
confidence: 70%
“…Gil [8] reported 1.7% uncertainty in his work. C D measurement accuracy can be increased to 0.05% [10]. The drag reduction is often measured in Count, which is equal to 0.001 C D change compared to the initial.…”
Section: Aerodynamic Dragmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma actuator reduce drag by redirect the air flow around the rear edges, controlling the flow structure in the wake as shown in Figure 5. Meanwhile Hui et al, [11] stated in their paper that when ions collide with neutral particles in the gas around the actuator, the local momentum of airflow in the region is increased and ionic wind is induced thus injecting momentum into the boundary layer. It was observed that the drag reduction (DR) using this flow control becoming less effective at higher wind speed due to limitation of increasing actuator voltage.…”
Section: Active Flow Control 21 Plasma Actuatormentioning
confidence: 99%
“…Comparing the control effects of linear and serpentine plasma actuators on the rear flow field of the tractor-trailer truck by Roy et al [33], it was found that the former fails to reduce the drag, while the latter has a big change in the drag, and obtained the drag drops by more than 14% and 10% at an inflow velocity of 26.8 and 31.3 m/s. At the same time, some researchers use plasma actuators to control the airflow separation on the rear window of the Ahmed model, so as to achieve the purpose of reducing drag [34][35][36].…”
Section: Introductionmentioning
confidence: 99%